2016
DOI: 10.1111/ijcp.12910
|View full text |Cite
|
Sign up to set email alerts
|

Absorbent products use and symptom distress in women who have urinary incontinence and heart failure

Abstract: To provide interventions that reduce distress from UI in women already burdened with a serious chronic disease, clinicians must screen women who have HF for UI. Clinicians must also actively listen to how women manage UI, explore their perceptions about importance to get treatment, and understand their expectations for that treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A study exploring the effect of absorbent product use on the distress caused by UI in women diagnosed with heart failure revealed that absorbent products were commonly used in women with severe UI. The authors have concluded that using absorbent products indirectly affects UI discomfort by changing how women see the necessity of seeking UI treatment (27).…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring the effect of absorbent product use on the distress caused by UI in women diagnosed with heart failure revealed that absorbent products were commonly used in women with severe UI. The authors have concluded that using absorbent products indirectly affects UI discomfort by changing how women see the necessity of seeking UI treatment (27).…”
Section: Discussionmentioning
confidence: 99%